Advancement in Multi-Functional Poly(styrene)-Poly(N-isopropylacrylamide) Based Core–Shell Microgels and their Applications. (3rd April 2018) - Naseem, Khalida; Begum, Robina; Wu, Weitai; Irfan, Ahmad; Farooqi, Zahoor H.
GRAPHICAL ABSTRACT: ABSTRACT: Core–shell microgels made of non-responsive polystyrene core and responsive poly(N-isopropylacrylamide) shell show exceptional properties as compared to homogenous microgels prepared by conventional methods. Due to the presence of solid polystyrene core, such type of microgels can be easily recycled from reaction mixture. Different methodologies adopted to prepare polystyrene-poly(N-isopropylacrylamide) based core–shell microgels have been described in this review article. Extraordinary properties of core–shell microgels induced due to the presence of solid polystyrene core have also been elaborated. Temperature responsive, feed contents tuned as well as charged-based characteristics of these core–shell microgels have also been discussed in detail. Various analytical techniques used to characterize these core–shell microgels have also been enlightened. Application of polystyrene-poly(N-isopropylacrylamide) based core–shell microgels as micro-reactor, efficient adsorbent for various type of proteins, source for synthesis of hollow microspheres for various applications, and catalysts in oxidation/reduction reactions have also been discussed critically in detail in this review article. Future directions of polystyrene-poly(N-isopropylacrylamide) based core–shell microgels have also been described to help researchers working in this field.